PELINDUNGAN HUKUM KREDITUR ATAS PERLAWANAN EKSEKUSI HAK TANGGUNGAN OLEH PIHAK KETIGA - Jannah, Rizki Nurul; Siregar, Mahmul; Sukarja, Detania (Universitas Muhammadiyah Ponorogo, 2024)
The existence of a counterclaim from a third party claiming ownership of the collateral is one of several challenges that are sometimes faced in implementing mortgage rights. The following analysis uses the case between PT. Bank Danamon Indonesia, Tbk with a third party (Henny Susanti, et al.) as the main discussion to examine the bank's rejection of the implementation of mortgage rights obtained by the third party. With this case analysis, it is hoped that the decision ratio used by the panel of judges can be studied in depth. This research uses legislative and case methods to provide normative and prescriptive legal research. The results of this research result in the conclusion that the regulation of the burden of third party land rights used as collateral for the bank's mortgage rights is equivalent to the burden of the collateral provided by the debtor. The bank can file a police report against the party who misuses the credit application process, and the bank can also file a civil lawsuit as a creditor with mortgage rights who has been harmed by the bank's negligence in determining the mortgage rights of a third party. In its legal analysis, the Panel of Judges at the Tangerang District Court prioritized formal elements. This does not apply to the Panel of Judges who have applied positive law correctly at the appeal, cassation and PK levels.